ПРЕЦИЗИОННЫЙ ИЗМЕРИТЕЛЬ ДИЭЛЕКТРИЧЕСКИХ ПАРАМЕТРОВ ВЫСОКОВОЛЬТНОЙ ИЗОЛЯЦИИ ПОД РАБОЧИМ НАПРЯЖЕНИЕМ - Борщев , П.И.; Ободовский, В.Д. (Інститут електродинаміки НАН України, Київ, 2014)
Device for measuring of difference of loss factors and capacitance ratio of the high-voltage insulations under operating voltage is described. Influence of voltage between points grounding insulations and device is suppressed by electrical isolation of power and control of the measuring channels. Excludes current transformers, whereby reduced error measurement of loss factor. References 4, figures 2.